1997
DOI: 10.1097/00004872-199715040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mortality by ambulatory blood pressure monitoring versus screening blood pressure measurements

Abstract: The ambulatory blood pressure had a stronger predictive power for mortality than did the screening blood pressure. This appears to have been the first study of the prognostic significance of ambulatory blood pressure monitoring versus screening blood pressure measurements in a general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
145
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(155 citation statements)
references
References 28 publications
7
145
0
3
Order By: Relevance
“…The independent prognostic value of ambulatory BP, which was also confirmed in the present study, has been demonstrated by several previous investigators. [1][2][3][4] However, ambulatory BP monitoring is primarily used to evaluate risk in subjects with known office hypertension. Whereas white-coat hypertension has been subject to numerous investigations during previous years, the knowl- edge about the opposite phenomenon, isolated ambulatory hypertension, is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The independent prognostic value of ambulatory BP, which was also confirmed in the present study, has been demonstrated by several previous investigators. [1][2][3][4] However, ambulatory BP monitoring is primarily used to evaluate risk in subjects with known office hypertension. Whereas white-coat hypertension has been subject to numerous investigations during previous years, the knowl- edge about the opposite phenomenon, isolated ambulatory hypertension, is limited.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Although 24-hour ambulatory BP recordings more accurately reflect the 24-hour BP load imposed on the vascular bed, most commonly, risk assessment in clinical practice and evaluation of antihypertensive treatment effect in clinical trials are based on conventional office BP monitoring. When there is a discrepancy between office and ambulatory BP, as in white-coat hypertension, the prognosis has been suggested to be more closely related to ambulatory BP.…”
mentioning
confidence: 99%
“…4 -6 So far, only 1 large study has examined the prognostic value of ambulatory BP in a general population, the Ohasama study, conducted in a Japanese population, found future cardiovascular deaths to be better predicted by ambulatory BP than office BP. 7,8 In 1993 to 1994, we recorded ambulatory BP in a random sample of 1700 men and women from the general Danish population. Survival status was recorded until October 2003, allowing us to study the relationship between ambulatory BP and mortality in a general Western population for the first time.…”
mentioning
confidence: 99%
“…Ademais, Gould e col verificaram que os valores de pressão intra-arterial também se correlacionam melhor com as medidas realizadas em casa do que com as medidas do consultório 7 . Além disso, também foi demonstrado que as medidas da pressão em casa correlacionam-se melhor com mortalidade do que as medidas de consultório 8 .…”
unclassified